Oral Submucous Fibrosis - A changing scenario - Tinky Rose; Anita Balan (Wolters Kluwer Medknow Publications, 2007)
Tobacco causes a wide spectrum of diseases. Its use is the world's leading cause of death accounting for four million deaths per year. There is a general concept among the younger generation that chewing tobacco (spit tobacco, smokeless tobacco) is safe or less harmful than smoking, which has led to an increase in tobacco chewing habit. Chewable tobacco is a greater health hazard having 24 - 30% higher tobacco content. In addition to oral cancer chewing tobacco leads to impaired functions of heart, nerves, brain and altered hormonal activities. Users of manufactured tobacco products like gutkha, pan parag etc. also present with an increasing incidence of oral submucous fibrosis; of concern is that this is of early onset. In this context patients coming to the OP clinic of Oral Medicine and Radiology, Dental College, Trivandrum were screened for OSF during the period Jan 2003 - Oct 2003. The clinical presentation of OSF in patients using these manufactured smokeless tobacco products or Betel quid spices was documented and were compared with the results of a similar study conducted in the department during the period May 1993 to Feb 1994.